(untitled) (Research, Society and Development, 2023)
The use of correct management in soybean crop is essential for obtaining adequate levels of productivity, with the soil being extremely important when seeking economic returns. Thus, the objective of the study was to analyze the efficiency of using soil conditioner in two soils with different textures, in order to obtain information that can express the best dose to be used, to obtain productive gains in the crop. The work was carried out in two different locations, the first area being located in the municipality of Ouro Verde do Oeste – PR, with approximately 65% clay and the second area being located in the municipality of Terra Roxa – PR, with approximately 15% clay. 5 treatments were carried out, with different doses of the conditioner: Control; 250 kg ha-1; 500 kg ha-1; 750 kg ha-1 and 1000 kg ha-1, distributed in a randomized block design in a 2 x 5 factorial scheme. Incidence of soil diseases, number of nodules, root dry mass, number of branches, plant height were evaluated, number of pods per plant, number of grains per plant, mass of one thousand grains and productivity. Significant differences were found using the Tukey test for the variables; disease incidence, number of nodules, root dry mass, thousand grain mass and soybean crop productivity. Significant differences were also obtained between the areas of study for all variables evaluated. The dose of 1000 kg ha-1 guaranteed an increase in soybean crop productivity for Terra Roxa.